The depression cure : the 6-step program to beat depression without drugs - Ilardi, Stephen S., 1963- (Cambridge, MA : Da Capo Lifelong, 2009)
Most Americans work long hours, eat on the fly, and lead increasingly sedentary, isolated lives. Alongside this lifestyle, depression rates have skyrocketed: approximately 1 in 4 Americans will suffer from major depression at some point in their lives. Where have we gone wrong? The author sheds light on our current predicament and reminds us: our bodies were never designed for the sleep deprived, poorly nourished, frenzied pace of twenty-first century life. In fact, our genes have changed very little since the days of our hunter-gatherer ancestors and are still building, in effect, Stone Age bodies. Herein lies the key to breaking the cycle of depression. Inspired by the extraordinary resilience of aboriginal groups like the Kaluli of Papua New Guinea (who rarely suffer from depression), the author prescribes a program that harks back to what our bodies were originally made for, and need. Here you can find the road back to lasting health by integrating the following 6 elements into your life: an omega-3 rich diet; exercise; plenty of natural sunlight; ample sleep; social connections; and participation in meaningful tasks that leave little time for negative thoughts, all things that our ancestors had in abundance. -- From publisher.
Understanding depression. The epidemic and the cure ; Making sense of depression ; Treating depression : the state of the art (and science) -- Therapeutic lifestyle change : the six steps. Brain food ; Don't think, do ; Antidepressant exercise ; Let there be light ; Get connected ; Habits of healthy sleep -- Making the change. Putting it all together ; When roadblocks emerge : a troubleshooting guide.
Includes bibliographical references (pages 259-275) and index.
Keywords: Depression, Mental -- Alternative treatment; Self-actualization (Psychology); Nonfiction